Hume's Relevant Epistemology. In Defence of ``The Old Hume'' - Novotny, Zdenek (Civilia, 2016)
Hume's philosophy of knowledge is contained in Book I ``Of the Understanding'' of his Treatise of Human Nature (The Old Hume) and in his Enquiry concerning Human Understanding (The New Hume). The dispute about philosophical relevance of these two works has become topical again recently, and there is a growing number of Humean commentators who rather prefer the Enquiry which is certainly better in style. It is undoubtedly also easier for readers, free of some formal imperfections of the Treatise, and although - as a whole - it is a good deal shorter than Book I of the Treatise, one third of its contents is new, so that it is a substantially different book. But unlike the Treatise, it neglects such philosophical questions as those of space and time, the distinction between mind and the external world, substance (both material and spiritual), and even the idea of personal identity. The ``theory of ideas'' and operations with them as well as the popular discussion of causation and probability is shortened and simplified in the Enquiry. The logical structure and systematic method of the Treatise is lost in the later work, and the ambition to confront and possibly solve deep problems of human knowledge is abandoned here. The Treatise, in comparison with the Enquiry, must be, therefore, regarded as a book of first-rate philosophical importance and relevant for the assessment of Hume's epistemology. But there is still an interpretational problem about the two works.
Keywords: Hume; Epistemology; Treatise; Enquiry; comparison; philosophical importance